HISTORY OF MUTUALLY BENEFICIAL COOPERATION BETWEEN UZBEKISTAN AND THE UNITED STATES OF AMERICA IN SCIENCE AND EDUCATION - Rahmatov, Ilgor (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2020)
This article provides information about the work done between Uzbekistan and the United States in the field of science and education over the years of independence, their importance. Cooperation between the two countries in the field of science and education has been analyzed historically and chronologically, the results of many projects have been summed up.